Lower Limb Ischemia: Aortoiliac Thrombosis Related to Antiphospholipid Syndrome (APS)—Case Report and Review of the Literature - Arnaldo Toffon; Raffaella Piovesan; Consolato Francesco Minniti; Omar Caruso; Paolo Criscenti; Sabina Villalta; Maurizio Cavallo (Case Reports in Surgery)
Antiphospholipid syndrome (APS) is recognized as one of the main determinants of hypercoagulable conditions. The literature reports the incidence of this syndrome in a third of patients who underwent surgery for peripheral revascularization. Antiphospholipid antibodies are divided into two categories in relation to specific diagnostic tests. The first group is called lupus anticoagulant and consists of immunoglobulins that inhibit the phospholipid dependent coagulation tests in vitro. The second group is defined by their ability to conduct the phospholipid in an ELISA test. The occurrence of thrombotic events in patients with systemic erythematosus lupus (SEL) and anticoagulant antibodies was described for the first time in 1963 by Bowie. The discovery of anti-cardiolipin antibodies in antiphospholipid syndrome is due to Harris et al. who described the syndrome. Primitive APS was consequently defined in the absence of further underlying illnesses. In this disease, arterial thrombosis occurs mainly in the brain. Peripheral arteries are affected less frequently. Thrombosis of the great vessels is reported as anecdotal.